Subclinical Atherosclerosis in Systemic Sclerosis: Not Less Frequent Than Rheumatoid Arthritis and Not Detected With Cardiovascular Risk Indices - SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT; DİRESKENELİ, RAFİ HANER (WILEY, 2016)
Objective. To determine the frequency of subclinical atherosclerosis in patients with systemic sclerosis (SSc; scleroderma) compared to healthy subjects (HS) and rheumatoid arthritis (RA) patients and to determine the ability of cardiovascular (CV) risk indices in detecting SSc patients with subclinical atherosclerosis. Methods. A total of 110 SSc patients (102 females and 8 males, mean +/- SD age 50.5 +/- 11.9 years), 110 age-and sex-matched RA patients, and 51 HS without CV disease were examined with ultrasonography (US). Carotid intima-media thickness (cIMT) >0.90 mm and/or carotid plaques were used as the gold standard for subclinical atherosclerosis (US+). Systematic Coronary Risk Evaluation (SCORE), QRisk II, and 2013 American College of Cardiology (ACC)/American Heart Association (AHA) CV risk indices were calculated. Results. Twenty-one (19.1%) SSc patients, 24 (21.8%) RA patients, and 3 (5.9%) HS had subclinical atherosclerosis (SSc versus RA: P=0.62, SSc versus HS: P=0.029). cIMT in SSc was higher compared to HS (0.68 +/- 0.15 mm versus 0.61 +/- 0.10 mm; P=0.008) but similar to RA patients (0.66 +/- 0.14 mm; P=0.82). Subclinical atherosclerosis in SSc was associated with age (odds ratio [OR] 1.07, P=0.013), elevated erythrocyte sedimentation rate (OR 3.4, P=0.045), and pulmonary arterial hypertension (OR 4.27, P=0.012). Concerning CV risk indices, of the 21 US+ SSc patients only 0, 3 (14.2%), and 6 (28.6%) were classified as high CV risk according to SCORE, QRisk II, and ACC/AHA risk indices, respectively. Conclusion. Subclinical atherosclerosis in SSc patients is more frequent than in HS, but is as frequent as in RA patients in which accelerated atherosclerosis is clearly defined. CV risk indices for the general population are considerably insufficient to detect SSc patients with atherosclerosis.
Keywords: INTIMA-MEDIA THICKNESS; CORONARY-ARTERY CALCIFICATION; ENDOTHELIAL DYSFUNCTION; LUPUS-ERYTHEMATOSUS; HEART-DISEASE; SCORE; PREVALENCE; MORTALITY; DEATH; INVOLVEMENT